Gender differences in Climate risk Perception, weather information needs and willingness to pay for climate advisory services by livestock farmers in Senegal. - Houessionon, Prosper; Worou, Nadine; Chan, Derek; Toukap, Pietrick Arnaud Mengaptche; Wane, Abdrahmane; Whitbread, Anthony M. (2023)
This study examines climate risk perception, weather information needs, and willingness to pay for climate advisory services among Senegalese livestock farmers. In a sample of 600 farmers, results reveal a substantial perception of risks [HP(1] related to high temperatures, drought, and decreasing rainfall, with women demonstrating a higher overall risk perception than men. Age-wise, younger farmers exhibit heightened risk perception. The utility function analysis indicates preferences for integrated advisory services and market information. Livestock farmers express a willingness to pay 410 FCFA per month for climate advisory services with market information and substantially higher amounts (880-980 FCFA) for integration of indigenous knowledge, scientific forecasts, and pastoral resource advisories. These findings offer insights crucial for tailoring effective climate adaptation strategies in Senegal's livestock sector.